Legal Analysis Of Legal Protection Of Workers' Rights Based On Unilateral Termination Of Employment By PT Fast Food Indonesia (KFC Indonesia) - Siagian, Afny Azzahra; Amanda Fauzi, Rizka; Haptoro, Dyanhza Aji; Susanti, Pipi; Yamani, M. (jurnal.unprimdn.ac.id, 2025)
This article discusses unilateral termination of employment (PHK) by employers is a practice that still often occurs in the world of employment in Indonesia and raises legal issues, especially related to the protection of workers' rights. This study analyzes legal protection for workers in the case of unilateral layoffs carried out by PT Fast Food Indonesia (KFC Indonesia), and assesses its legal implications for the mechanism for resolving industrial relations. The issues raised include the suitability of unilateral layoffs with the provisions of Law Number 6 of 2023 and the extent to which workers' rights are legally protected. This study uses a normative legal method with a statutory approach and a case approach. Data were obtained through literature studies and analysis of real cases of mass layoffs by KFC Indonesia. The results of the study indicate that unilateral layoffs by the company do not comply with legal procedures as stipulated in Article 151 of Law Number 6 of 2023, which requires notification, bipartite negotiations, and settlement of industrial relations disputes. In addition, workers' rights such as severance pay and job loss guarantees are not provided proportionally. The legal implications put workers in a disadvantaged position and pave the way for dispute resolution through legal mechanisms in the Industrial Relations Court. This study emphasizes the importance of enforcing strict and comprehensive legal protection for workers in facing unilateral layoffs.